Information Structuring Begins with the Numeration - Aboh, Enoch Oladé (IBERIA: An International Journal of Theoretical Linguistics, 2010)
This paper argues for the strong minimalist view that information structure starts in the numeration in the form of discourse-related lexical items which drive the derivation. Though sometimes covert, these discourse-related particles encode features, such as, Interrogative force, Topic, or Focus and display very specific structural behavior indicating that they project in syntax. The analysis further demonstrates that these features are comparable to other optional formal features (e.g., Case, -features) that are added arbitrarily when the lexical item enters the numeration.